COMPREHENSIVE ANALYSIS OF FILTER AND ROUTER TRANSFORMATION - Jayapradha J., Lakshmipriya M., Vathana D. (International Journal of Advanced Science and Technology, 2020)
Data Warehouses are central repositories of integrated data from a wide range of sources. Various operational systems load the data in the Data warehouse. In this paper, we present how the data are loaded into the data warehouse using Filter and Router Transformation in Informatica. The main aim is to analyze the performance level of Filter and Router Transformation with multiple different conditions. The Filter Transformation loads the filtered data into the corresponding target table and drops the other data that do not satisfy the requirement. The Router Transformation filters out the irrelevant data to the separate target and relevant data to a different target table. Unlike Filter Transformation, router transformation provides you the flexibility of populating multiple targets depending upon the different types of conditions. Also, we have computed the time complexity of Filter and Router Transformation for a different position of records.